UTILIZATION OF CITRUS MEDICA FOR THE REDUCTION OF NITRATENITROGEN FROM AQUEOUS SOLUTION - M., Mayilsamy; M., Santhiya; V., Swabna; Muthunarayanan, Vasanthy (Malaysian Journal of Science, 2011)
The objective of this study is to investigate the reduction of nitrate-nitrogen from aqueous nitrate-nitrogen solution containing 30 ppm of nitrate-nitrogen using the leaves of Citrus medica in a powdered form. The reduction was found to be 85% from 30 ppm nitrate-nitrogen containing solution. The mechanism of the reduction could be attributed to the antioxidant property of the Citrus medica leaves, which is found to be contributed by the flavonoids of the leaf material. This is confirmed by the DPPH activity of Citrus medica which signifies the H+ ion donation to the nitrate-ions thereby facilitating reduction. The powdered leaves of Citrus medica were subjected to FT-IR analysis too which reveals certain changes in the peaks obtained for 2920 and 2855 cm- Â¹. (Keywords: Nitrate-nitrogen; Citrus medica; aqueous solution; Reduction; Antioxidant)